Internalization of Pancasila Values in a Hospitality Character Education as a Weltanschauung for Gen Z: A Tourism College Perspective - Teddy Chandra; Samad Chakour; Keiko Himeno; Narendra Duhita (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study examines how Pancasila values are internalized in hospitality character education for Generation Z students at Politeknik Pariwisata NHI Bandung. The study responds to the need for tourism higher education to produce graduates who are not only technically competent, but also ethically responsible, culturally rooted, and globally prepared. Using a qualitative case study design, data were collected through non-participant observations, document analysis, and institutional data review focused on Catur Prasetya, AHLAK, GRADES, and the Global Code of Ethics for Tourism. The data were analyzed thematically by identifying, categorizing, and interpreting patterns related to value internalization, hospitality character, and professional identity formation. The findings show that Pancasila values are internalized through four complementary pathways. Catur Prasetya functions as a normative foundation that builds civic-professional responsibility, institutional loyalty, discipline, and national awareness. AHLAK translates moral values into professional orientations such as trustworthiness, hospitality, loyalty, adaptability, and collaboration. GRADES operates as a daily habituation mechanism that makes character visible through greeting, respect, attitude, discipline, empathy, and smile. The Global Code of Ethics for Tourism extends Pancasila-based character education toward global ethical concerns, including sustainability, cultural respect, community welfare, human dignity, workers’ rights, and stakeholder responsibility. This study contributes to character education and hospitality education by conceptualizing Pancasila as a professional weltanschauung for tourism higher education. The proposed framework connects national philosophy, institutional culture, behavioral habituation, and global tourism ethics in shaping Gen Z hospitality character. It offers practical guidance for strengthening value-based education in vocational tourism institutions.